Fortified Wheat-Rye Bread: Investigating the Impact of Processing Purple Potatoes “Vitelotte” on Physicochemical and Sensory Attributes - Wilk, Marta; Bartczak, Marcelina; Kaim, Urszula (Wpływ obróbki fioletowych ziemniaków „Vitelotte” na właściwości fizykochemiczne i sensoryczne wzbogaconego chleba pszenno-żytniego, 2023)
Cereal products, including bread, are significant in global consumption, confirmed by their enduring presence in human diet. However, commonly consumed refined flour bread contains only small amounts of essential nutrients and bioactive compounds necessary for optimal health. The study aimed to investigate the influence of the method of processing purple potatoes used as an addition to sourdough wheat-rye bread on its physicochemical properties. This study investigated the incorporation of purple potatoes into wheat-rye bread using three distinct processing methods: boiling, baking and raw (C, B, and R). Polyphenol content, crumb colour analysis, acidity determination, salt and sugar content quantification, porosity evaluation, moisture content determination, and bread volume were measured, and organoleptic assessment was also conducted. The highest content of polyphenolic compounds in bread (207.45 mg GAE/100 g of bread) was obtained by using roasted purple potatoes as an additive. The bread had suitable physicochemical parameters and was classified in the first group of bread quality in the organoleptic tests. The results highlighted the importance of potato incorporation in bread formulations, affecting both quality and nutritional attributes, thus offering promising avenues for developing functional foods.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 125-135
Keywords: purple potatoes; Vitelotte; wheat-rye bread; sourdough; fioletowe ziemniaki; chleb pszenno-żytni; zakwas